Analisis Kepentingan Rusia Dalam Konflik Republik Abkhazia Dan Republik Ossetia Selatan Dengan Georgia - Muhammad Ilham Maulana (2020)
The conflict between Abkhazia and South Ossetia with Georgia is a long-standing conflict in the Caucasus Region. The conflict that was originally an internal conflict in Georgia turned into a global conflict because of the involvement of Russia and other countries. This conflict does not only involve the two regions with Georgia but, the involvement of other international actors and Russia as a big country in the South Caucasus in the conflict has full of interests in the conflict and the South Caucasus, which makes this research interesting is that intervention by Russia is not only aimed at ending the conflict but they are trying to reach interests in the South Caucasus and Russia's intervention as a whole influences the course of the conflict. The purpose of this research is to find out the interests of Russia as long as they intervene in conflicts involving Abkhazia and South Ossetia with Georgia. The research method used by the authors in this study is qualitative research with data collection methods using secondary data or literature studies and this research is supported by the theory of National Interest, Geopolitical Theory, and the concept of Military Intervention. From this study, the authors found that Russia was successful. Russia succeeded in helping Abkhazia and South Ossetia and maintaining their influence in Georgia and the South Caucasus.